2015
DOI: 10.1007/s12035-015-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Interacts with Caveolin-1 to Facilitate Autophagy-Lysosome-Mediated Claudin-5 Degradation in Oxygen-Glucose Deprivation-Treated Endothelial Cells

Abstract: Using in vitro oxygen-glucose deprivation (OGD) model, we have previously demonstrated that 2-h OGD induces rapid, caveolin-1-mediated dissociation of claudin-5 from the cellular cytoskeletal framework and quick endothelial barrier disruption. In this study, we further investigated the fate of translocated claudin-5 and the mechanisms by which OGD promotes caveolin-1 translocation. Exposure of bEND3 cells to 4-h OGD, but not 2-h OGD plus 2-h reoxygenation, resulted in claudin-5 degradation. Inhibition of autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 45 publications
(74 reference statements)
10
55
1
1
Order By: Relevance
“…There are differences between the experimental models used in our study and those used by Li et al While we used 18-h OGD in cells and 24-h MCAO in rats, they used 6-h OGD/4-h reoxygenation in cells and 2-h ischemia/22h reperfusion in rats. Supporting our findings, a recent study by Liu et al demonstrated that another BBB component claudin-5 is degraded by 4-h OGD, but not by 2-h OGD/2-h reoxygenation, and suggested that the degradation of claudin-5 is mediated by caveolin-1 and autophagy-lysosome activation in endothelial cells [38]. However, in vivo experiments were not performed in the study by Liu et al We believe that these previous observations along with our current findings contribute to an integrated understanding of the role of autophagy in ischemic BBB dysfunction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There are differences between the experimental models used in our study and those used by Li et al While we used 18-h OGD in cells and 24-h MCAO in rats, they used 6-h OGD/4-h reoxygenation in cells and 2-h ischemia/22h reperfusion in rats. Supporting our findings, a recent study by Liu et al demonstrated that another BBB component claudin-5 is degraded by 4-h OGD, but not by 2-h OGD/2-h reoxygenation, and suggested that the degradation of claudin-5 is mediated by caveolin-1 and autophagy-lysosome activation in endothelial cells [38]. However, in vivo experiments were not performed in the study by Liu et al We believe that these previous observations along with our current findings contribute to an integrated understanding of the role of autophagy in ischemic BBB dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrated that ischemia-induced autophagy mediated the degradation of occludin and that inhibition of autophagy by 3-MA reversed occludin degradation and attenuated BBB dysfunction. In line with our observation, claudin-5 was degraded by autophagy-lysosome activation in OGD-exposed brain endothelial cells [38], and autophagic activation with BBB damage were observed in p50 knockout mice [39], suggesting that autophagy may contribute to ischemic neuronal and vascular damage. It is also demonstrated that enhanced autophagy during brain ischemia in diabetic mice might be responsible for excessive BBB disruption [40].…”
Section: Discussionsupporting
confidence: 90%
“…NO can induce autophagy lysosome-mediated claudin-5 degradation in oxygen-glucose deprivation-treated endothelial cells. 42 However, we found here that NO does not induced autophagy at the time and dose used in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…In the present study, the level of claudin-2, a cation specific pore forming TJ protein was found to be reduced in ClC-2 over-expressing cells. Though caveolin-1 is known to interact with claudins [32] [55], further studies are needed to delineate the role of ClC-2 in the modulation of claudin-2 protein level.…”
Section: Discussionmentioning
confidence: 99%